PENGARUH LITERASI KEUANGAN, GAYA HIDUP DAN PENGGUNAAN UANG ELEKTRONIK TERHADAP PERILAKU KONSUMTIF GENERASI MILENIAL KOTA DENPASAR - Wensensius Ngampus; Ni Luh Wayan Sayang Telagawathi; Fridayana Yudiaatmaja (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to examine the effect of financial literacy, lifestyle and use of electronic money on consumptive behavior, both partially and simultaneously. The approach used is quantitative using survey methods. The population in this study is the millennial generation of Denpasar City who are in the age range of 22-42 years. This research uses probability sampling technique in taking samples and using random sampling method. The number of samples is 100 people. Data was collected using a component questionnaire in the context of financial literacy, lifestyle, use of electronic money and consumer behavior. Data were analyzed using multiple linear regression tests. The results showed that: (1) financial literacy has a significant negative effect on the consumptive behavior of the millennial generation in Denpasar City, (2) lifestyle has a significant positive effect on the consumptive behavior of the millennial generation in Denpasar City, (3) the use of electronic money has a significant positive effect on the consumptive behavior of the next generation millennials in Denpasar City, (4) financial literacy, lifestyle and use of electronic money jointly influence the consumptive behavior of the millennial generation in Denpasar City. Thus these three factors influence the consumtive behavior of the millennial generation in Denpasar City.